Mechanoluminescnce and photoluminescence in gamma irradiated NaCl:Eu - Kalra, M; Dhoble, S J; Kher, R S (Recent Research in Science and Technology, 2012)
Rare earth (RE) ions posses unique optical behavior when doped into phosphors. Eu2+ activated phosphors find use in many applications. Eu2+ emission arises from the lowest band of 4f6 5d configuration to 8S7/2 state of 4f7. NaCl having different concentrations of Eu were prepared by melt technique. The crystals of small sizes were cleaved from the grown crystal block and crushed to obtain powder or microcrystalline form of NaCl. Annealed samples were exposed to gamma rays at dose level 0.930kGy. Mechanoluminescnce (ML) was excited impulsively by dropping a load of mass 0.4 kg with the impact velocity of 0.6 ms-1 on to it. An intense ML peak was observed in its ML glow curve. ML intensity increases with increasing concentration of dopant. ML emission spectrum shows a single peak at 482 nm. Photoluminescence (PL) of the sample has also been recorded and a single peak at 427 nm was observed. Shift in ML and PL emission spectrum was observed.